Protection of minority shareholder interests, cross-listings in the United States, and subsequent equity offerings - Reese, William A; Weisbach, Michael S (Journal of Financial Economics, 2002)
This paper examines the hypothesis that non-US firms cross-list in the United States to increase protection of their minority shareholders. Cross-listing on the NYSE or Nasdaq subjects a non-US firm to a number of provisions of US securities law, and requires the firm to conform to US GAAP. It therefore increases the expected cost to managers of extracting private benefits, and commits the firm to protect minority shareholders’ interests. The expected relation between the quantity of cross-listings and shareholder protection in the home country is ambiguous, because managers will consider both expected private benefits and the public value of their shares. However, there are clear predictions about the relation between subsequent equity issues, shareholder protection, and cross-listings:(1)Equity issues increase following all cross-listings, regardless of shareholder protection.(2)The increase should be larger for cross-listings from countries with weak protection.(3)Equity issues following cross-listings in the US will tend to be in the US for firms from countries with strong protection and outside the US for firms from countries with weak protection.We find evidence consistent with each of these predictions. Overall, the desire to protect shareholder rights appears to be an important reason why some non-US firms cross-list in the United States.